2012
DOI: 10.1177/1545968312446003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Modified Constraint-Induced Movement Therapy Versus Conventional Therapy for Upper Extremity Rehabilitation After Stroke

Abstract: Two hours of CIMT may be more effective than conventional rehabilitation in improving motor function and use of the paretic arm in patients with chronic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 44 publications
1
91
0
5
Order By: Relevance
“…It is important to note that two weeks of physical therapy alone are not able to induce a significant clinical improvement in the chronic phase of stroke (Kwakkel and Kollen, 2013), while in our study such an improvement was observed following two weeks of physical therapy coupled with cerebellar iTBS. This finding seems consistent with the findings of previous studies showing that motor improvements in chronic stroke patients are due not only to conventional therapy, but also to the application of rehabilitation programs, including innovative and adjunctive techniques such as constraint-Induced movement therapy (Smania et al, 2012) and robot-assisted therapy (Lo et al, 2010). The current study presents some limitations.…”
supporting
confidence: 75%
“…It is important to note that two weeks of physical therapy alone are not able to induce a significant clinical improvement in the chronic phase of stroke (Kwakkel and Kollen, 2013), while in our study such an improvement was observed following two weeks of physical therapy coupled with cerebellar iTBS. This finding seems consistent with the findings of previous studies showing that motor improvements in chronic stroke patients are due not only to conventional therapy, but also to the application of rehabilitation programs, including innovative and adjunctive techniques such as constraint-Induced movement therapy (Smania et al, 2012) and robot-assisted therapy (Lo et al, 2010). The current study presents some limitations.…”
supporting
confidence: 75%
“…IIb B [688][689][690][691][692][693][694] Bilateral upper limb training has not been as well studied as CIMT. Two meta-analyses and more recent trials suggest that there is a small but measurable benefit compared with no intervention, but no consistent evidence of superiority over other task-specific training interventions has been shown.…”
Section: Iib Bmentioning
confidence: 99%
“…References: (a) 33-35, 37, 38, 43, 45, 46, 49, 50, 57, 62, 64, 70, 71, 73, 80, 82; (b) 39, 42; (c) 55, 73; (d) 46, 82; (e) 46, 75; (f) 28; (g) 31, 33- 43, 45- 47, 51-56, 73, 75-78, 80-82; (h) 28; (i) 34, 37, 41, 43, 46, 52, 54, 55, 57, 61-64, 70-73, 75, 77, 78, 80-82; (j) 67, 69; (k) 28; (l) 34, 36, 37, 41, 43, 46, 49-52, 54, 55, 57, 61, 62, 64, 70-73, 75, 77, 78, 80-82; (m) 67, 69, 79; (n) 41, 47, 52, 54, 62-64, 66, 71; (o) 53, 81, 82; (p) 81, 82.…”
Section: Figurementioning
confidence: 99%